Long-term effects of comprehensive school health on health-related knowledge, attitudes, self-efficacy, health behaviours and weight status of adolescents - Nicole Naadu Ofosu; John Paul Ekwaru; Kerry Ann Bastian; Sarah A. Loehr; Kate Storey; John C. Spence; Paul J. Veugelers (BMC, 2018)
Abstract Background APPLE Schools is a Comprehensive School Health (CSH) project, started in schools in socioeconomically disadvantaged areas where dietary habits are poor, physical activity (PA) levels are low, and obesity rates are high. Earlier research showed program effects whereby energy intake, PA and weight status of students in APPLE Schools had reached similar levels as that of students in other schools. However, it is unknown whether the effects of CSH are sustained when children grow into adolescents. Effects of APPLE Schools on health-related knowledge, attitudes, self-efficacy, diet, PA, and weight status, seven years after the start of the project, when students were in junior high and high school were assessed. We hypothesised that APPLE School graduates and comparison school graduates will remain at similar levels for these indicators. Methods In the 2015/16 school year, junior high and high school graduates (grades 7-12) in Northern Alberta, Canada participated in a Youth Health Survey. Participants included graduates from APPLE elementary schools (n = 202) and comparison elementary schools (n = 338). Health-related knowledge, attitudes, self-efficacy, diet (24-h dietary recall), PA (pedometer step count) and weight status were assessed. Mixed effects regression was employed to assess differences in these outcomes between APPLE School graduates and comparison school graduates. Comparisons between elementary school (2008/09) and junior high/high school (2015/16) of self-efficacy, PA and weight status were also conducted. Results APPLE School graduates did not significantly differ from comparison school graduates on any outcomes (i.e. knowledge, attitudes, self-efficacy, diet, PA, and weight status). Additionally, no significant differences existed in the comparisons between 2008/09 and 2015/16. Conclusion Our findings of no difference between the APPLE School graduates and comparison school graduates suggest that the effects of APPLE Schools may continue into adolescence or the new school environment may have an equalizing effect on the students. Since lifestyle practices are adopted throughout childhood and adolescence, and the school environment has an important influence on development, an extension of CSH initiatives into junior high/high schools should be considered. This will help to consolidate and support the continuance of healthy lifestyle messages and practices throughout childhood and adolescence.